2014
DOI: 10.1590/s0102-86502014000700007
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of abdominal electroacupuncture on oxidative stress and inflammation due to testis torsion/detorsion in rats

Abstract: Conception, design, intellectual and scientific content of the study, critical revision, final approval of the manuscript. ABSTRACT PURPOSE:To evaluate the effects of acupuncture (Ac) and electroacupuncture (EAc) on oxidative stress and inflammation in testis torsion/detorsion (T/D) model in rats. METHODS:Thirty male Wistar rats were randomized into five groups. G1 Group (Sham) served as control. The remaining groups were submitted to spermatic cord torsion (720°) for 3 hours, followed by detorsion and reperfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…However, TEAS treatment initiated at 2 days after irradiation significantly increased the levels of SOD2 and GSH-Px and decreased the level of MDA, leading to an improved antioxidant capacity of ovarian tissue. Recent studies have reported 7that electroacupuncture pretreatment can attenuate ovarian oxidative stress in rodent models [44, 45]. Accordingly, our study proved that blocking oxidative stress is another mechanism by which TEAS rescues the X-irradiation-induced ovarian follicular loss.…”
Section: Discussionsupporting
confidence: 70%
“…However, TEAS treatment initiated at 2 days after irradiation significantly increased the levels of SOD2 and GSH-Px and decreased the level of MDA, leading to an improved antioxidant capacity of ovarian tissue. Recent studies have reported 7that electroacupuncture pretreatment can attenuate ovarian oxidative stress in rodent models [44, 45]. Accordingly, our study proved that blocking oxidative stress is another mechanism by which TEAS rescues the X-irradiation-induced ovarian follicular loss.…”
Section: Discussionsupporting
confidence: 70%
“…It has been shown that acupuncture can reduce oxidative stress in different conditions [34]. Acupuncture not only has preventive and repairing effects through antioxidation and anti-oxidative stress action [35] but also decreases the inflammatory responses [36].…”
Section: Discussionmentioning
confidence: 99%
“… [ 22 ] Rat model Suture 2 h Scrotal incision 1,2, and 3 months Zinc 1, 2, and 3 months after ischemia Oral 0.016 ml/rat Zinc attenuated I/R-induced oxidative stress and histological damage in the ipsilateral and contralateral testes … [ 181 ] Rat model Suture 4 h Scrotal incisions 4 days Zinc Aspartate 210 min post ischemia Intraperitoneal 50 mg/kg Zinc aspartate ameliorated I/R testicular injury by preventing increase oxidative stress … [ 70 ] Rat model Suture 1 h Scrotal incision 1 h Zinc sulfate and melatonin 21 days before ischemia Intraperitoneal 5 and 3 mg/kg respectively Zinc sulfate and melatonin ameliorated I/R testicular injury when used singly and combined. This is associated with an improved spermatogenic activities and antioxidant status Others [ 182 ] Rat model Suture 3 h Scrotum 4 h Acupuncture/eletroacupuncture 5 min post ischemia Bilaterally 2 Hz or 10 Hz Acupuncture/eletroacupun-cturereversed reversed I/R-induced ↓MDA, MPO [ 183 ] Rat model Suture 5 min Scrotum …”
Section: Pharmacological Potentials In the Management Of I/r Injurymentioning
confidence: 99%